Enhancing Physical Education for Learners with Visual Disabilities: Instructional Practices and Inclusive Strategies - Jakinda, Rose; Munayi, Simon; Chumba, Janet; Gathoni, Benson (African Journal of Education and Practice, 2025)
Purpose: The study sought to discover what is going on in the classroom for learners with visual disability. This study examines the instructional practices employed by physical education teachers to support learners with visual disabilities. The objective was to identify and analyze the teaching strategies used to facilitate effective instruction in physical education for this group. The research question guiding the study was: What instructional practices are employed in the teaching of physical education for learners with visual disabilities? Findings from this study have the potential to inform educational stakeholders and contribute insights that support policy formulation, enhancing instructional strategies for learners with visual disabilities and fostering a more inclusive learning environment. In this study, instructional practices refer to teaching techniques such as the use of lesson plans, adherence to the syllabus, and direct interaction between teachers and learners to ensure meaningful engagement and learning experiences. Methodology: This study utilized a descriptive survey research design to assess physical education instruction for learners with visual disabilities. Descriptive research systematically examines populations, situations, or phenomena by addressing key questions such as when, what, where, and how, making it an appropriate approach. The study collected both qualitative and quantitative data, incorporating insights from key informants, including head teachers. Findings: This study found that physical education teachers for learners with visual disabilities consistently used lesson plans derived from schemes of work, which were routinely inspected by head teachers. While most teachers considered lesson time sufficient, a minority raised concerns about time constraints affecting students' ability to meet learning objectives. Schools followed the general Competency-Based Curriculum (CBC) syllabus, requiring teachers to adapt it to students' needs, though standardization of these adaptations remains unclear. Learners responded positively to instruction, particularly enjoying game-based activities, but physical education was not among their top three favorite subjects, with inadequate equipment and resources cited as challenges. Unique Contribution to Theory, Practice and Policy: The study recommends further investigation into time allocation, standardized syllabus adaptations, and improved access to teaching materials to enhance instructional effectiveness and inclusivity.